A review of hyperandrogenism state in polycystic ovarian syndrome - M., Mohamed Shabi; P. S., Nivya; C. S., Devika; Reddy, Malayanur Suhas; N., Poornima; K. R., Roopesh; Joseph, Joel; Kolageri, Shivanand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Polycystic ovary syndrome is one of the most prevalent endocrinopathy in premenopausal women. The pathophysiology of PCOS is not clear, however disturbance in the hypothalamic-pituitary-ovarian axis and abnormal steroidogenesis along with genetic and environmental factors act as main contributors to this disorder. The steroidogenic pathway is affected by the overexpression of the CYP11A, CYP17, and CYP19 genes in PCOS, which results in a hyperandrogenic condition. The initial effect of too much androgen in PCOS is impaired folliculogenesis. The most frequent clinical manifestations of hyperandrogenism in women with PCOS include hirsutism, acne, and androgenic alopecia. Women with PCOS may have an excess of androgen during foetal life due to the elevated expression of P450c17a during the whole pregnancy. PCOS is believed to be formed in utero by the influence of androgen excess on gene expression in adolescence and adulthood, which offers more solid evidence that real PCOS can be induced by prenatal androgenization. A prenatal androgen excess-induced epigenetic phenomena is suggested by the current theory of PCOS’s developmental genesis. It is currently believed that the many tiny follicles seen in polycystic ovaries and the considerable irregularity in the very early stages of folliculogenesis are associated to the formation of anovulation in PCOS.